2002
DOI: 10.1046/j.1365-2591.2002.00477.x
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro comparison of the bactericidal efficacy of lethal photosensitization or sodium hyphochlorite irrigation on Streptococcus intermedius biofilms in root canals

Abstract: The combined use of a photosensitizing agent and a low power laser directed at the access cavity was bactericidal to S. intermedius biofilms in root canals but was unable to achieve total kill, unlike 3% NaOCl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
106
1
17

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(130 citation statements)
references
References 48 publications
3
106
1
17
Order By: Relevance
“…14 Several studies have shown that oral bacteria are sensitive to photodynamic therapy (PDT). 15,16 In recent years, in vitro [17][18][19][20][21][22][23][24][25][26] and in vivo [27][28][29] studies have been performed to investigate the antibacterial effect of the PDT on the microorganisms in root canal. Most of these studies have focused on the PDT capability as a complementary technique besides the conventional endodontic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…14 Several studies have shown that oral bacteria are sensitive to photodynamic therapy (PDT). 15,16 In recent years, in vitro [17][18][19][20][21][22][23][24][25][26] and in vivo [27][28][29] studies have been performed to investigate the antibacterial effect of the PDT on the microorganisms in root canal. Most of these studies have focused on the PDT capability as a complementary technique besides the conventional endodontic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In this therapy, certains dyes such as Toluidine blue, Methylene blue, Azuline paste, Tolonium chloride and light source such as Diode laser, 35-mW helium-neon low power laser [15], Gallium-aluminium arsenide (Ga-Al-As) diode laser can be used.…”
Section: Discussionmentioning
confidence: 99%
“…However, common sense dictates that higher concentrations will achieve reduction in bacterial load faster owing to the presence of a higher concentration of chloramine molecules.It should also be kept in mind that the more concentrated solutions of NaOCl are thicker and subsequently there is less wetting of the canal walls. (16) It has been observed that NaOCl solutions at concentrations of 0.5%, 3% and 5% degrade the organic phase (collagen) of dentine with no loss of mineral, possibly leading to brittleness of endodontically treated teeth. (14) There are significant biological toxicity risks if NaOCl is expressed under pressure into the periodontal ligament space.…”
Section: Sodium Hypochloritementioning
confidence: 99%